Intellectual Property Based Financing: Juridical Review of Government Regulation Number 24 of 2022 And Relevance of Establishing Intellectual Property Rights Appraisal Institution - Sulistianingsih, Dewi; Al Fikry, Ahmad Habib; Setiawan, Andry (Kosmik Hukum, 2023)
The issuance of Government Regulation Number 24 of 2022 is the hope for achieving an advanced national economy through the utilization of intellectual property rights asÂ  collateral objects in bank and non bank financial institutions. However, this is faced with the absence of an intellectual property rights appraisal institution in Indonesia. This paper aims to: (i) explain intellectual property-based financing arrangements based on Government Regulation Number 24 of 2022; and (ii) describes the establishment of an intellectual property rights appraisal institution in Indonesia. The author uses a normative juridical research method with a statutory and comparative approach. The results of the writing show that: 9i) Government Regulation Number 24 of 2022 regulates intellectual property-based financing schemes through bank and non-bank financial institutions; and (ii) the discourse on establishing an institution to assess intellectual property rights in Indonesia trough laws and regulations. This independent institution functions to set standards for valuing intellectual property rights and valuing intellectual property rights to be used as collateral for financing trough bank and non-bank financial institutions. Â 